The analysis of factors affecting municipal employees' willingness to report to work during an influenza pandemic by means of the extended parallel process model (EPPM) - Carolin von Gottberg; Silvia Krumm; Franz Porzsolt; Reinhold Kilian (BMC, 2016)
Abstract Background The management of pandemics with highly infectious diseases in modern urban habitats depends largely on the maintenance of public services. Understanding the factors that influence municipal employees' willingness to come to work during a pandemic is therefore a basic requirement for adequate public health preparedness. In this study the extended parallel process model (EPPM) is applied to investigate how the readiness of municipal employees to report to work during an influenza pandemic (IP) is affected by individual attitudes and environmental conditions. Methods 1.566 employees of a major German city participated in a cross-sectional online survey. The questions of the survey covered the dimensions of risk perception, role competence, self-efficacy, role importance, sense of duty, and willingness to report to work in the case of an IP. Data were analysed by means of path analyses. Results Data suggest that up to 20 % of the public service workers were not willing to come to work during an IP. Willingness to report to work was increased by the perception of a high working role competence, a high assessment of role importance, high self-efficacy expectations, and a high sense of duty. Negative effects on willingness to report to work were identified as the perception of a high risk to become infected at work and the perceived risk to infect family members. The decomposition of direct and indirect effects provided important insights into the interrelationships between model variables. Conclusions Measures to increase municipal workers' willingness to report to work in case of an infectious pandemic should include communication strategies to inform employees clearly about their particular tasks during such critical events and training exercises to increase their confidence in their competences and skills to fulfil these tasks.